1995
DOI: 10.1116/1.588128
|View full text |Cite
|
Sign up to set email alerts
|

Etching of GaAs/AlGaAs rib waveguide structures using BCl3/Cl2/N2/Ar electron cyclotron resonance

Abstract: An anisotropic nonselective etch for GaAs/AlGaAs rib waveguides has been developed for use under electron cyclotron resonance conditions. The plasma chemistry features BCl3 to minimize AlGaAs oxidation effects and small additions of N2 to induce sidewall protection when using photoresist masks. The fundamental mode attenuation in GaAs/AlGaAs waveguides is sensitive to the choice of both plasma chemistry and masking material, but can be reduced to ≤1 dB cm−1 for channel widths of 4–5 μm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Typically, in a chlorine chemistry, aluminium oxide can only be removed by physical etching (i.e. sputtering), while other regions of the sample are still subject to the chemical etching species, thus leading to increased surface roughness [12]. BCl 3 is a strongly reducing agent which reacts with aluminium oxide and is also able to neutralize water vapour in the reactor chamber [13], thereby preventing reoxidation of the AlGaAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, in a chlorine chemistry, aluminium oxide can only be removed by physical etching (i.e. sputtering), while other regions of the sample are still subject to the chemical etching species, thus leading to increased surface roughness [12]. BCl 3 is a strongly reducing agent which reacts with aluminium oxide and is also able to neutralize water vapour in the reactor chamber [13], thereby preventing reoxidation of the AlGaAs.…”
Section: Introductionmentioning
confidence: 99%
“…When using a photoresist mask, it has been shown that etching AlGaAs with BCl 3 chemistry (with Ar or neon (Ne)) can passivate sidewalls via the re-deposition of BCl x fragments, etch products and resist-containing residues [20,21]. N 2 is a common additive to chlorine species to intentionally degrade resists in order to produce sidewall passivation with a polymer deposition [12,21,22]. Even though the passivation layers created during dry etching of photoresist-protected microstructures using Cl 2 and/or BCl 3 chemistries with N 2 are attractive, they cannot be adapted to the fabrication of sub-micron features.…”
Section: Introductionmentioning
confidence: 99%